Головний кооперативний комітет у відносинах кооперації з державою в УСРР 1920-х років - Гладкий, С.О. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматривается история создания и деятельности в УССР 1920-х годов специального государственного органа управления кооперацией - Главного кооперативного комитета при СНК УССР. Анализируются его состав и порядок формирования, компетенция и полномочия, роль во взаимоотношениях кооперативных организаций с государством, развитии кооперативного законодательства, функционировании кооперативной системы. Освещаются отношения государственные ведомств по поводу ликвидации Главного и окружных кооперативных комитетов на этапе свертывания новой экономической политики. In article the history of creation and activity in USSR 1920th years of special state controls by cooperation - the Main cooperative committee is considered. Its structure and the order of formation, the competence and powers, a role in mutual relations of the cooperative organizations with the state, development of the cooperative legislation, functioning of cooperative system are analyzed. Relations of the state departments concerning liquidation of the Main thing and district cooperative committees at a stage of curtailing of new economic policy are covered.